¿What is the impact of studying in any of the different modules in technical schools? a multilevel analysis of performance on PSU, Science Test, in 2018 (Revista INTEREDU11, 2022)
The present study aims to determine the differences in the performance in the University Selection Exam (PSU for its acronym in Spanish), Science test for the Technical Education module, amongst students from different areas of professional technical training. In order to establish the expected average score for students belonging to the technical areas, such as Commercial, Industrial, Technical and Services, Agricultural and Maritime, mixed-multilevel models were used (n = 18100 students who presented the PSU test in 2018). All data collected was sectorized by Region to understand the effect within a given territory. The results indicated that not all professional technical areas displayed the same level of performance in this tests, evidencing variations between -14 to 13 points for the different branches. Finally, it is argued that students of Technical Education Centers require a more appropriate assessment strategy to measure their learning, and also, that the quality of learning in these areas should be improved.